Use of technology by people with dementia and informal carers during COVID‐19: A cross‐country comparison. (25th August 2022) - Chirico, Ilaria; Giebel, Clarissa; Lion, Katarzyna; Mackowiak, Maria; Chattat, Rabih; Cations, Monica; Gabbay, Mark; Moyle, Wendy; Pappadà, Alessandro; Rymaszewska, Joanna; Senczyszyn, Adrianna; Szczesniak, Dorota; et al.
Abstract: Objectives: Considering the adverse outcomes of COVID‐19, it is essential to provide adequate support and care for people with dementia and informal carers. Technology can reduce the distress associated with social distancing rules and the decreased access to in‐person services. This study aimed to explore the use of technology and its perceived effects across different settings and countries. Methods: The sample was composed of 127 informal carers and 15 people with dementia from the UK, Italy, Australia and Poland. Semi‐structured interviews explored participants' experiences of using technology and their perceived effects. Transcripts were analysed by researchers in each country using an inductive approach. Results: Three overarching themes were developed: (1) Technology kept us alive during COVID‐19; (2) Remote care was anything but easy; (3) Perceived technology limitations. Many similarities emerged between countries supporting the role of technology for being socially engaged, having a routine, and staying active. However, the benefits of technology for health and psychosocial care were more limited. Across countries, barriers to the access and use of technology included lack of digital literacy, dementia severity, and lack of appropriate digital environments. Help and supervision from carers were also necessary and sometimes perceived as an additional burden. Conclusions: Technology can effectively reduce the shrinking world that may be amplified by the pandemic, thus preserving people with dementia's social skills and maintaining family connections. However, for more extensive and well‐adapted use of technology in dementia care, actions should be taken to overcome the barriers to the access and use of technology by older and vulnerable people globally. Key points: During COVID‐19 technology allowed people with dementia and informal carers to be socially engaged, have a routine, and stay active. Benefits of technology in dementia health and psychosocial care were limited. Barriers to the access and use of technology included lack of digital literacy, dementia severity, and lack of appropriate digital environments. The pandemic should prompt actions towards a more extensive and well‐adapted use of technology in dementia care.